The effect of bacterial vaginosis on HIV infection - Abrahams, Bianca (Department of Integrative Biomedical Sciences (IBMS), 2024)
Human Immunodeficiency Virus-1 (HIV) and Bacterial Vaginosis (BV) are both among the most common diseases affecting young women in Sub-Saharan Africa. BV is characterised by dysbiosis in the female reproductive tract (FRT) when optimal Lactobacillus spp. such as L. crispatus, are displaced by anaerobes such as Gardnerella spp., consistently isolated from the FRT of BV-positive women. Gardnerella spp. produce a number of important virulence factors such as vaginolysin (VLY) and sialidase and are known to initiate the formation of biofilms and hence, contribute to the pathology associated with BV. As many studies have suggested that BV increases susceptibility to HIV infection, it stands to reason that Gardnerella spp. might either indirectly, (initiate the onset of BV and subsequent immune responses) or directly (via its virulence factors) play a role in enhancing HIV acquisition. This study investigated whether VLY, sialidase and biofilm formation played a role in HIV infection. Recently, it was discovered that Gardnerella spp. comprises G. leopoldii, G. vaginalis, G. piotii and G. swidsinskii as well as nine other genome species which vary in virulence potential. When we compared twenty strains isolated from BV-positive women belonging to G. vaginalis (n = 16), G. piotii (n = 2) and G. swidsinskii (n = 2), we found differences in the presence, expression, and activity of VLY and sialidase as well as biofilm-forming capacity between the strains, suggesting a wide range in virulence. However, there was no overt association between HIV infection and Gardnerella virulence factors. Gardnerella sialidase consists of three isoforms: NanH1, NanH2 and NanH3 and as the latter is responsible for the sialidase activity in the FRT, nanH3 was cloned, expressed in E.coli and purified by His-Tag affinity chromatography. We found that purified, recombinant NanH3 increased HIV infection in vitro, most likely by removing the sialic acid moieties on the surface of host cells, reducing the negative repulsive force between the viral Envelope and cell membrane. This may then facilitate virus accumulation at the cell surface, favouring attachment to CD4 and/or its co-receptors and thereby enhance HIV infection. Interestingly, only the two G. piotii strains expressed NanH3, suggesting that perhaps only some species of Gardnerella may play a role in enhancing HIV infection. This has important implications for diagnosis and treatment as BV-positive women shown to carry G. piotii strains, might benefit from preexposure prophylaxis with antiretroviral drugs.